Estimation of Prevalence Rates of the Acute Coronary Syndrome (ACS) among Patients Presented with Chest Pain in the Cardiac Center - Masroor Anwar, Muhammad Nazim, Shahid Hussain Memon, Sumair Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chest pain has been observed in the number of peoples. This is the major cause of hospital visit. Objective: The purpose of the study was to observe the acute coronary syndrome prevalence. The association of the chest pain with the cardiovascular risk factors was also studied. Study design: It is an observational study with statistical approach, conducted at Wazirabad Institute of Cardiology, Wazirabad and Khyber Teaching Hospital, Peshawar. Material and Methods: The study was conducted from Dec 2021 to May 2022. The 101 patients visited the teaching hospital of our department were included in the study. Focusing on the history of hypertension diabetes and smoking all the participants involved in the study were interviewed. The acute coronary syndrome prevalence rates were calculated. In order to find the correlation of the variables with the ACS the linear regression analysis was performed. Results: The calculated mean age was observed to be 54± 16.5 years. Out of all the patients included in the study the 75% were male participants, rest of them were female. The hypertension symptoms were observed in the 37% patients. The diabetes were observed in 26% while 23% patients were smokers. The 50% patients had non-specific chest pain while 31% patients had atypical chest pain. The 18% patients had the typical chest pain. There were total 33% patients that were suffering from acute coronary syndrome. Among these patients there were 7% patients that had unstable angina and 10% had NSTEMI, with only 17% patients suffering from STEMI. The positive correlation of acute coronary syndrome with smoking hypertension age, gender was observed. Conclusion: ACS is the lethal forms of pain. It causes serious health issues especially in patients above 40 years. The prevalence of ACS and its link with chest pain in patients at the tertiary health center was analyzed. The prevalence of the disease has strong connection with the risk factors. Keywords: Acute coronary syndrome (ACS), hypertension, atherosclerotic plaque, chest pain and risk factor.